Intimate partner violence in pregnancy: Communicate better to unveil the problem. - Moreira, Rosa Maria Santos (2016)
The intimate partner violence (IPV) is defined as any behavior within an intimate relationship that causes physical, psychological or sexual damage to members of relationship (Organización Panamericana de la Salud, Oficina Regional para las Américas de la Organización Mundial de la Salud 2003). Exposure to the IPV during pregnancy leads to a number of risk factors with significant impact on the physical, mental and social well-being of women, as well in perinatal outcomes. The prevalence rates, existing throughout the world, have demonstrated the importance of further enhance the attention given to the woman / couple / family, from prenatal care to the postpartum. (World Health Organization, WHO Collaborating Centre for Violence Prevention 2010), challenges the health professionals to monitor the phenomenon of IPV and compare national and international indicators in order to adjust and qualify interventions. This requires awareness of health professionals in the early identification of these indicators using appropriate communication strategies and safe environments.